Evaluating safety and effectiveness of the early-onset sepsis calculator to reduce antibiotic exposure in Dutch at-risk newborns: a protocol for a cluster randomised controlled trial - Frans B Plötz; Marijke C van der Weide; Bo M van der Weijden; Niek B Achten (BMJ Open, 2023)
Introduction Newborns are at risk for early-onset sepsis (EOS). In the Netherlands, EOS affects less than 0.2% of newborns, but approximately 5% are treated with empirical antibiotics. These numbers form an example of overtreatment in countries using risk-factor based guidelines for administrating antibiotics. An alternative to these guidelines is the EOS calculator, a tool that calculates an individual EOS risk and provides management recommendation. However, validation outside the North-American setting is limited, especially for safety outcomes. We aim to investigate whether EOS calculator use can safely reduce antibiotic exposure in newborns with suspected EOS compared with the Dutch guideline.Methods and analysis This protocol describes a cluster randomised controlled trial assessing whether EOS calculator use is non-inferior regarding safety, and superior regarding limiting overtreatment, compared with the Dutch guideline. We will include newborns born at ≥34 weeks’ gestation, with at least one risk factor consistent with EOS within 24 hours after birth. After 1:1 randomisation, the 10 participating Dutch hospitals will use either the Dutch guideline or the EOS calculator as standard of care for all newborns at risk for EOS. In total, 1830 newborns will be recruited. The coprimary non-inferiority outcome will be the presence of at least one of four predefined safety criteria. The coprimary superiority outcome will be the proportion of participants starting antibiotic therapy for suspected and, or proven EOS within 24 hours after birth. Secondary outcomes will be the total duration of antibiotic therapy, the percentage of antibiotic therapy started between 24 and 72 hours after birth, and parent-reported quality of life. Analyses will be performed both as intention to treat and per protocol.Ethics and dissemination This trial has been approved by the Medical Ethics Committee of the Amsterdam UMC (NL78203.018.21). Results will be presented in peer-reviewed journals and at international conferences.Trial registration number NCT05274776.